Frontal suspension for congenital ptosis using an expanded polytetrafluoroethylene (Gore-Tex®) sheet: one-year follow-up - Nakauchi K (Dove Medical Press, 2013)
Kazuaki Nakauchi,1 Hidenori Mito,2 Osamu Mimura11Hospital of Hyogo College of Medicine, Hyogo, 2Ide Eye Hospital, Yamagata, JapanBackground: The frontalis suspension technique is the surgical method of choice in patients with ptosis and a levator function of 4 mm or less. Several types of materials have been used, including Gore-Tex®, which has been used successfully as a frontalis sling material since 1986. Recently, a Gore-Tex sheet (wider than a sling or strip) suspension was reported. This paper reports the results of 27 eyes from 20 patients with congenital ptosis treated using the frontalis suspension technique with the newly developed Gore-Tex Most Versatile Patch (MVP) sheet.Methods: All patients underwent surgery between April 2007 and September 2011 and were followed up for at least one year. The average follow-up duration was 18 months, with a range of 12–36 months. The average patient age was 45 (5–85) years, and the group included 11 males and nine females. Thirteen cases demonstrated ptosis in one eye, and seven cases involved both eyes. The patients were divided by age into a younger group and an older group. All ptosis procedures were performed using the Gore-Tex MVP sheet. The implant was normally 7 mm wide for adults and 5 mm wide for children. The implantation method was the same as that used for the sheet shape fascia.Results: In all patients, satisfactory functional results were observed at the 6-month follow-up examination. Eyelid opening heights were also obtained. The average marginal reflex distance (MRD) was -0.5 mm preoperatively, which improved to +1.9 mm after surgery. After one year, average MRD was +1.6 mm. MRD attenuation was more frequent in the younger group. There were no cases requiring redo surgery and only one case of exposure.Keywords: polytetrafluoroethylene, Gore-Tex®, frontalis suspension, congenital ptosis, recurrence